Patterns of ‘Black Medicine’ Utilization under the National Health Insurance Law in Israel - Ronen, Rozenblum (Marketing & Menedzsment, 2019)
The current study explores the patterns of black medicine in Israel, following the enactment of the National Health Insurance Law in 1995. The data and the findings reflect the perception, attitude and assessment of the two key factors of the existence of the phenomenon: Doctors in public hospitals on the one hand and patients on the other. The study is based on questionnaires completed by patients and doctors, as well as on a comparison of some of the data from Noy’s (1997) research, prior to the enactment of the above law.